High temperature stiffening of ferroelastic LaCoO3. Issue 11 (September 2019) - Orlovskaya, N.; Lugovy, M.; Verbylo, D.; Reece, M.J.; Graule, T.; Kuebler, J.
Abstract: The cyclic ferroelastic hysteretic behavior of pure LaCoO3 perovskite ceramic has been studied at different temperatures in four point bending. The stress-strain deformation behavior of LaCoO3 was analyzed both in the term of the maximum stress in the cycle and in terms of the temperature used when the cyclic testing was performed. The characteristics of the stress-strain hysteresis loops, such as hysteresis loop area and irreversible strain, as well as effective Young's modulus, were analyzed, and it was established that both the loading and the temperature history have a significant influence on the mechanical behavior of LaCoO3 . Young's modulus values are reported to be much higher in the 700–900 °C temperature range as compared to the measurements performed in the RT-400 °C temperature range.